Factors associated with neonatal hypoxic ischemic encephalopathy in infants with an umbilical artery pH less than 7.00. (May 2019) - Barrois, Mathilde; Patkai, Juliana; Delorme, Pierre; Chollat, Clément; Goffinet, François; Le Ray, Camille
Abstract: Objective: Our objective was to identify factors associated with hypoxic-ischemic encephalopathy (HIE) among newborns with an umbilical pH < 7.00. Study design: Case-control study during a four-year study period in a single academic tertiary-center, including all neonates ≥35 weeks with an umbilical pH < 7.00. Cases were neonates with HIE, regardless of Sarnat classification, and controls were neonates without signs of HIE. We used univariate and multivariate analysis to compare the maternal, obstetric, and neonatal characteristics of cases and controls. Results: Among 21, 211 births, 179 neonates≥35 weeks (0.84%) had an umbilical pH < 7.00. One hundred and forty-seven(82.1%) newborns had severe asphyxia without HIE, 32(17.9%) had HIE and 21(11.7%) needed therapeutic hypothermia. Neonates with HIE were significantly more likely to have 5-minute Apgar score<7(75% versus 15.7% P < 0.01), together with a lower mean umbilical arterial pH (6.84 versus 6.95, P < 0.01) and lower mean base deficits (-17.0 versus -12.7, P < 0.01). Factors significantly associated with HIE were the mother being overweight(28.1% for cases versus 14.3% for controls, adjusted OR=4.6[1.4–15.2]) or obese(25.0% versus 13.6%, aOR=15.5[1.1–12.5]), smoking(18.7% versus 5.4%, aOR=5.8[1.6–21.2]), a sentinel event as cord prolaps or placenta abruption (34.4% versus 13.6%, aOR=2.7[1.1–7.2]), and decreased fetal heart rate variability(68.7% versus 44.2%, aOR=2.8[1.1–6.9]). Conclusion: Among neonates with an umbilical cord pH < 7.00, those with HIE had a more severe metabolic acidosis. Maternal factors associated with HIE among newborns with an umbilical pH < 7.00, were being overweight or obese, and smoking, and the associated obstetric factors were a sentinel event and decreased fetal heart rate variability.